PEMANFAATAN KOMPOS TANDAN KOSONG KELAPA SAWIT DENGAN BAKTERI SELULOLITIK DAN LIGOLITIK SERTA NPK TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Isna Rahma Dini; Idwar Idwar; Amir Franky Simamora (Jurnal Agroekoteknologi, 2019)
ABSTRACTCocoa (Theobroma cacao L.) is one of the large plantations after oil palm. Theincrease in cocoa nursery can be accompanied by the utilization of waste derivedfrom palm oil, namely oil palm empty fruit bunches (OPEFB). oil palm emptyfruit bunches can be useful as organic fertilizer because it can improve soilphysical, chemical and biological properties. The use of OPEFB as organic fertilizer will also reduce excessive use of NPK. Utilization of OPEFB into organic fertilizer can be in the form of compost or raw OPEFB organic matter plus cellulolytic and lignolytic microbes. This study aims to determine the effectof NPK fertilizer and OPEFB compost on the growth of cocoa seedlings. Thisresearch was conducted experimentally using a completely randomized designconsisting of nine treatments and three replications. Parameters of observationwere plant height, stem diameter, number of leaves, root canopy ratio, dry weight of seedlings and age of planting. The results showed that the provision of 100 g polybag-1 OPEFB compost plus 50% NPK fertilizer (2 g polybag-1) could provide good growth in cocoa seeds (Theobroma cacao L.).